A Literature Review: Factors Affecting Parental Behaviour in Early Detection of Children with Retinoblastoma - Qur'aniati, Nuzul; Sutianingsih, Sutianingsih; Kurnia, Iqlima Dwi; Rachmawati, Praba Diyan; Mundakir, Mundakir (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2024)
Introduction: In Indonesia, retinoblastoma is a type of cancer with a high incidence and is the most common cause of death after leukaemia. Early detection of retinoblastoma in children is a health practise that involves identifying or screening for retinoblastoma symptoms in order to avoid consequences. However, a delay in early detection contributes to the high prevalence of disease metastases and negative consequences. This literature review aims to look at the factors affecting parental behaviour in early detection of children with retinoblastoma.Methods: This literature review searched three databases, including Web of Science, PubMed, and Google Scholar, for publications published between 2016 and 2020. The PICOS framework was utilised to set inclusion criteria while reviewing papers. The 14 papers fulfilled the inclusion criteria and. The Joanna Briggs Institute Critical Appraisal were utilised to assess study quality.Results: The review's findings revealed that parental behaviour in early detection of children with retinoblastoma is influenced by internal and external factors. The internal factors include parents' or caregiver' socioeconomic status, level of education, individual beliefs, and the age at which a child receives his or her initial diagnosis. Then, the examples of external factors include distance, the support of a healthcare provider, and the source of health information.Discussion: Internal and environmental factors influence parental behaviour in the early detection and treatment of retinoblastoma. Early detection of retinoblastoma can be sped up by providing information about early symptoms, time of diagnosis, risk factors, complications, and therapy.